Development of lacustrine primary productivity in the Amazon Basin during the Holocene. (July 2022) - Soares, Juliano HF; Moreira, Luciane S; Turcq, Bruno; Moreira-Turcq, Patricia; Sifeddine, Abdel; Dornellas, Nayara; Evangelista, Heitor; Nogueira, Juliana; Aniceto, Keila; Martins, Gabriel S; Kury, Milena S; Brandini, Nilva; et al.
The Amazon Basin is one of the most productive regions in the world and an important carbon sink. However, lake productivity has varied throughout the Holocene, as preserved in lacustrine sedimentary records. Concentrations of chlorophyll pigmented derivatives that are mainly derived from phytoplankton and macrophyte populations can be used to infer lake production levels. Here we use the chlorophyll derivatives concentrations analyzed by spectrophotometer in sediment cores from nine lakes distributed throughout the Brazilian Amazon Basin to document the continental-scale changes in lake production during the Holocene. Chlorophyll derivatives have varied with changes in precipitation rate throughout the last 10, 000 years, similar to other climate records in tropical South America, including Ti concentration from the Cariaco Basin, δ 13 C from Lake Titicaca, and refractory black carbon in Nevado Illimani. Increasing precipitation is responsible for increasing the nutrient supply into the lake, which stimulates primary production. Our analysis was compared to climate-related parameters, suggesting an increasing trend of lake production rates during the wetter Late and Early Holocene, while lower production rates characterized the dry phase of the Middle Holocene. Therefore, the chlorophyll derivatives concentrations generally follow precipitation changes in the Amazon Basin during the Holocene.